Implementation of Sharia Marketing Characteristics for Gold Pawn Customers at Bank Mitra Syariah Gresik - Fitriyah, Zahrotul; Ardyansyah, Farid (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Purpose: Business competition is generally fierce, making it difficult for competitors or similar companies to attract customers. Some competitors may focus more on satisfying rather than optimising profits. The service must be done as well as possible to add value and attract customers. This study aims to see how Sharia marketing characteristics are implemented at Bank Mitra Syariah Gresik. Translated with DeepL.com (free version) Design/Method/Approach: This type of research is descriptive qualitative. Observation, interview, and documentation were applied as data collection methods. At this point, the researcher collects and organises the needed information, then presents the information according to the topic and summarises the findings, conclusions, and results based on the available evidence and data. Findings: Researchers use source triangulation to validate data. Sharia marketing has four characteristics at Bank Mitra Syariah Gresik: theoretical (rabbaniyah), realistic (al-waqi’yyah), ethical (al-akhlaqiyah), and humanistic (insanity), which have been implemented well. Originality/Values: This study highlights the real implementation of Sharia marketing characteristics at Bank Mitra Syariah Gresik, which positively impacts customer satisfaction. The theistic, ethical, realistic, and humanistic approaches have built a strong image and customer trust in Gold Pawn Services.